Efficacy and cost-effectiveness of an ACT and compassion-based intervention for women with breast cancer: study protocol of two randomised controlled trials {1} - Inês A. Trindade; Andreia Soares; David Skvarc; Diogo Carreiras; Joana Pereira; Óscar Lourenço; Filipa Sampaio; Bruno de Sousa; Teresa C. Martins; Paula Boaventura; Joana Marta-Simões; Mind Project Team; et al. (Trials)
Abstract Background Breast cancer is the most diagnosed cancer in women worldwide and carries a considerable psychosocial burden. Interventions based on Acceptance and Commitment Therapy (ACT) and compassion-based approaches show promise in improving adjustment and quality of life in people with cancer. The Mind programme is an integrative ACT and compassion-based intervention tailored for women with breast cancer, which aims to prepare women for survivorship by promoting psychological flexibility and self-compassion. A pilot study of the Mind programme has shown acceptability and preliminary efficacy in improving quality of life and psychological health. This paper presents the study protocol of two randomised controlled trials that aim to test the efficacy and cost-effectiveness of an optimised version of the Mind programme in women with breast cancer. Methods Participants will be women diagnosed with breast cancer randomly assigned to the Mind programme or a support group intervention (active control) in a 1:1 ratio for study 1, while study 2 includes one more arm (treatment as usual; inactive control) and a 2:2:1 ratio. Both interventions will be delivered weekly via an 8-session face-to-face or online group format. Data will be collected at baseline, post-treatment and 6-month follow-up. The efficacy and cost-effectiveness of the two interventions will be assessed. Treatment outcomes will comprise cancer-specific quality of life (primary outcome), anxiety and depressive symptoms, psychological flexibility, self-compassion, health-related quality of life, resource use, and intervention’s acceptability and feasibility. Study 1 will also include immunological and epigenetic markers associated with breast cancer prognosis and mental health. Outcome assessors will be blind to group allocation. Statistical analyses will be conducted using an intention-to-treat approach. Analyses of moderators and mediators of change will also be performed. Discussion These trials examine the efficacy and cost-effectiveness of an integrative ACT and compassion-based intervention tailored for women with breast cancer. Greater improvements in psychosocial, biological and resource use are expected in the Mind group, when compared to the control group(s). Results will likely support the potential benefits of the Mind programme for breast cancer patients and highlight the clinical relevance of integrative and holistic interventions in oncology. Trials registration {2a, 2b} ClinicalTrials.gov NCT05642897 and NCT06212414. Registered on December 8, 2022, and January 18, 2024.